People's Response on Land, Water and Biomass Development in Upper Kosi Watershed, Almora - Singh, Ashutosh (National Geographical Journal of India, 2022)
Land, water and biomass form the core of eco-development more specifically in watershed development. The watershed variables i.e. land, water and biomass do not operate individually rather they are interconnected. The emphasis on trio becomes much more important when it concerns with the rural economy as the triple F: food, fodder and fuel, the basic ingredients of livelihood depends on it. Increasing populations in the study area and consequent exploitation of the resources of the region is definitely bearing an impact on the fragile ecosystem of the study area. Present paper is an attempt to explain the people's perception of land, water and biomass development in Upper Kosi watershed, district Almora, Uttarakhand.